Avaliação experimental da atividade antitumoral da vacina peptídica anticâncer (vacina Hasumi®) - Pereira, Márcio Roberto Pinho (2003)
The Hasumi vaccine is based on peptides of plasmatic membrane of tumor cells and a extract of bovine spleen associated with immunostimulants substances. The aim of the present work was to evaluate the possible anticancer effect of the Hasumi vaccine and its mechanism of action in animals inoculated with experimental tumors. For the evaluation of the in vivo antitumoral activity, two groups of female Wistar rats were subcutaneously inoculated with 1.0 X 106 cells of the Walker 256 carcinossarcoma in the armpit area. The groups were subcutaneously vaccinated immediately with 500 µL of Hasumi vaccine (250 µL of peptides) or 500 µL of saline, and then, they received boosters of these doses every other day until their death. It was analyzed their survival function and the volume of tumor growth during the treatment period. The blood of these animals was taken for cell count. Other two groups of rats were also inoculated with 1.0 X 106 cells of the Walker 256 carcinossarcoma but they suffered surgical excision of the tumor 5 days after inoculation. After surgery, they received the same treatment of the above mentioned groups. In another set of experiments, four groups of mice C57BL/6 were inoculated with 1.0 X 106 melanoma B/16 cells maintained in culture. Three groups were subcutaneously vaccinated with 1 µL, 10 µL, 100 µL of Hasumi vaccine (0.006 g, 0.06 g, and 0.6 g of peptides) diluted in 200 µL of saline solution, and the fourth group received only 200 µL of saline. The animals received reinforcements of those doses every 7 days until their death. During the treatment, it was measured the volume of the tumor and the survival time of the animals. Other four groups of mice C57BL/6 were also treated in the same way that the previous groups, however the vaccination were performed by intraperitoneal injection. For the evaluation of the immunogenicity of the Hasumi vaccine, five groups of Swiss mice were immunized with 200 µL (100 µg of peptides) of Hasumi vaccine. Egg-albumine (100 µg) was used as positive control. The results showed that inoculated animals treated with Hasumi vaccine had their tumor partially inhibited. The total blood count revealed the Hasumi vaccine reverted the leukocytes rising observed in control group, suggesting an anti-inflammatory activity of the vaccine. The animals that suffered surgical retreat of the tumor plus vaccination also presented an inhibition of the tumor growth, and an animal was completely cured. The Hasumi vaccine was also active in mice inoculated with melanoma, and the vaccine seemed to be more efficient when injected intraperitoneally. The presence of antibodies IgG1 was verified by the method of PCA, indicating an immune answer of the Th2 type that is favorable to the anti-inflammatory activity, but it was not possible to detect antipeptides antibodies using ELISA assay. Our results suggest that Hasumi vaccine, as the most alike against cancer vaccines, shows an antitumor in vivo activity with some efficiency, suiting an induction of an immune response of Th2 type.